Structure-Activity Analysis and Microcapsule Stabilization of the Antioxidant Peptides from Tilapia Skin - Chunxiao MI; Lu YANG; Heqi YANG; Yue LIU; Xiaohui YU; Zibo HU; Yidi CAI; Xiang LI; Hui ZHOU; Long WU (Shipin gongye ke-ji)
To analyze the structure-activity relationship of antioxidant peptides and improve their stability, tilapia skin was enzymolized by double-enzyme stepwise enzymatic hydrolysis method. The DPPH· (2,2-diphenyl-1picrylhydrazyl), ABTS+· (2,2-biazo-bis(3-ethyl-benzothiazole-6-sulfonic acid) and hydroxyl radical (·OH) scavenging rates were used as evaluation indexes to isolate and screen the components with good antioxidant activity and analyze their structural characteristics. The peptide sequences were characterized by LC-MS/MS. The physicochemical properties were predicted by an online property prediction platform, and the docking sites of antioxidant peptides with DPPH· and ABTS+· were analyzed by molecular docking techniques. On this basis, to protect the core structure of antioxidant peptides, the enzymatic hydrolysis product was used as the core material, and sodium alginate chitosan as the wall material for microencapsulation, and the changes in stability and activity during simulated digestion in vitro were investigated. The results showed that the degree of hydrolysis of the products was 25.31%±0.51%, the yield was 61.66%±0.74%, and the radical scavenging IC50 of DPPH·, ABTS+· and ·OH were 3.82±0.28, 4.18±0.58 and 13.56±0.72 mg/mL. The online property platform predicted that 37 peptides out of 76 sequences were identified as non-toxic and potentially sensitizing. The structure-activity relationship of molecular docking analysis showed that the main mechanism of DPPH· removal was hydrogen transfer, electron transfer was the main mechanism of ABTS+· removal, Pro, Arg, Gly, Ala, Thr, Gln, and Tyr were the characteristic amino acids of DPPH· and ABTS+· removal. Hydrogen bonding and hydrophobic interaction were the main interactions between antioxidant peptides and free radicals. In addition, microencapsulation could protect the antioxidant activity of antioxidant peptides in the simulated digestive environment to a certain extent (DPPH·, ABTS+·, ·OH radical scavenging IC50 were 2.32±0.19, 2.99±0.14, and 27.41±0.50 mg/mL) and effectively resisted the degradation of gastric acid and protease, so that it had higher stability. Therefore, the selected peptides can be used as a new natural antioxidant, which providing a theoretical basis for exploring the mechanism of antioxidant peptides in tilapia skin and its development and application.